SUBVERSIVE IMAGINATION AND POSSIBILITIES OF CRITICAL AGENCY IN THE LANDSCAPES OF CODE? - Saariketo, Minna (AoIR Selected Papers of Internet Research, 2020)
This paper reflects the intertwinements of ‘agency’, ‘infrastructuration’, and ‘imagination’ in our increasingly networked technological everyday life. The focus of the research, navigating at the interfaces of critical media studies, domestication theory, STS, and critical software studies, is on the ways in which imaginations on agency are constructed and stabilized. Likewise, attention is directed to how societal power structures are produced, reproduced, and possibly challenged in the processes of constructing imaginaries of agency. To study the above mentioned perspectives together, critical cultural studies scholar Stuart Hall’s famous encoding/decoding model is applied and updated in the contemporary media technological context (Hall, 1973; 1980). Hall’s concept of ‘maps of meaning’ is brought in dialogue with the concepts of ‘sociotechnical imaginaries’ by Sheila Jasanoff and ‘social imaginaries’ by Charles Taylor. The multidisciplinary, multimethod, and multidata approach of the research sheds light on the diversity and complexity of imaginaries of agency in our times. Based on the results, it is suggested that there prevails an almost resigned sense of agency that many people share in relation to the conditions of their technologically mediated everyday life. Despite sporadic negotiations and dissonances, it seems that people have become accustomed to the idea that they have very little, if any, chances to influence the structures of their networked daily environments. It is suggested that future research should concentrate on making visible alternatives to modes of technology-related action as well as develop ways to challenge people to creatively (re)imagine the kind of technology they want to live with.